Metabolically healthy obesity (MHO) in the Malmö diet cancer study – Epidemiology and prospective risks. Issue 6 (November 2019) - Korduner, Johan; Bachus, Erasmus; Jujic, Amra; Magnusson, Martin; Nilsson, Peter M.
Abstract: Background/aims: Metabolically healthy obesity (MHO) remains controversial, since the underlying mechanisms behind this phenotype remain unclear. We aimed to investigate the characteristics of MHO, as well as prospective risks. Method: A cross-sectional analysis was carried out in a subsample of 3812 obese subjects selected from the Malmo diet cancer study (n = 28, 403). Subjects with MHO (n = 1182) were defined by having no records of hospitalization for somatic disorders prior to baseline examination. MHO subjects were further compared to subjects with metabolically unhealthy obesity, MUO (obese individuals with at least one recorded hospitalization: n = 2630), and all non-obese cohort controls (NOC; n = 24, 591). Moreover, prospective risk analyses for incident cardiovascular (CV) morbidity and mortality were carried out. Results: Compared to MUO individuals, MHO individuals reported a significantly lower proportion of sedentary life style (p = 0.009), but also significantly lower HbA1c (p = 0.012), fasting glucose (p = 0.001) and triglyceride levels (p = 0.011) than MUO. Cox-regression analysis (follow-up 20 ± 6 years) showed both a significantly lower all-cause mortality risk for MHO individuals as compared to MUO (p = 0.001), as well as lower incident CV morbidity risk (p = 0.001). When comparing MHO individuals to NOC, there were no significant differences in neither mortality risk nor incident CV morbidity risk. Conclusion: Compared to MUO individuals, MHO individuals presented with a higher level of physical activity, a more favorable lipid- and glucose profile and a lower prospective risk of total mortality and CV morbidity during 20-years follow-up. Notably, no significant differences could be seen in mortality and CV morbidity risks when comparing MHO subjects to non-obese controls.